Spatially interpolated PM2.5 concentrations for the US from 2006-2015 - O'Dell, Katelyn; Ford, Bonne; Fischer, Emily V.; Pierce, Jeffrey R. (Colorado State University. Libraries, 2019)
This dataset contains spatially interpolated daily PM2.5 concentrations observed by monitors in the Environmental Protection Agency's Air Quality System and non-smoke seasonal background PM2.5 estimates for 2006-2015. See the readme file for details on data processing and recommended usage.
Please note: The data files for years 2006, 2007, 2010, and 2013 were updated on 6/24/20 to correct errors identified by the first author.
Department of Atmospheric Science
Keywords: air quality; PM2.5; wildfire